Profit-loss Sharing Contract As An Alternative To Solve Unemployment In Sudan Through Investment In Livestock Breeding - Mahmoud Mohamed Ali Mahmoud Edris; Mohamed Sharif Bashir; Yusuf Sani Abubakar (ADDIN by Research Center of State Institute for Is, 2024)
Addin, Volume 17 Issue 2 Page (167–167)